2010
DOI: 10.3109/09513590.2010.488773
|View full text |Cite
|
Sign up to set email alerts
|

Premature ovarian failure from current perspective

Abstract: Premature ovarian failure (POF) is a syndrome characterised by amenorrhoea, hypoestrogenism and hypergonadotropinism before the age of 40. It is a disorder affecting approximately 1% of women <40 years, 1/1,000 women by the age of 30 and 1/10,000 women by the age of 20. POF is not merely an early menopause. Up to 50% of the patients with POF will have intermittent and unpredictable ovarian function which may persist for some years. Heterogeneity of POF is also reflected by the variety of possible causes, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 69 publications
1
59
0
3
Order By: Relevance
“…This may cause a significantly higher risk for osteoporosis and cardiovascular disease [40]. Therapies for the relief of symptoms and for decreasing the associated disease risks are currently based on hormone replacement, particularly estradiol [41]. A WHO study published in 2002, however, showed an increased risk of breast cancer, stroke, and heart disease associated with the use of estradiol-based hormone therapy and this has led many women to discontinue or choose not to receive treatment, although hormone-based therapy is still the most effective therapy available to date [42].…”
Section: Discussionmentioning
confidence: 99%
“…This may cause a significantly higher risk for osteoporosis and cardiovascular disease [40]. Therapies for the relief of symptoms and for decreasing the associated disease risks are currently based on hormone replacement, particularly estradiol [41]. A WHO study published in 2002, however, showed an increased risk of breast cancer, stroke, and heart disease associated with the use of estradiol-based hormone therapy and this has led many women to discontinue or choose not to receive treatment, although hormone-based therapy is still the most effective therapy available to date [42].…”
Section: Discussionmentioning
confidence: 99%
“…About 25% of POF cases are iatrogenic, being related to postsurgical ovarian failure and cancer treatments (radiotherapy and chemotherapy) [21][22][23]. It has been also hypothesized that POF may be induced by environmental factors, such as cigarette smoking, heavy metals, solvents, pesticides, plastics, industrial chemicals [21].…”
Section: Premature Ovarian Failure: the Terminologymentioning
confidence: 99%
“…It has been also hypothesized that POF may be induced by environmental factors, such as cigarette smoking, heavy metals, solvents, pesticides, plastics, industrial chemicals [21]. Moreover, there is evidence that POF can be secondary to infections (mumps, herpes zoster, cytomegalovirus), autoimmune (i.e., systemic lupus erythematosus, Hashimoto's thyroiditis, Addison's disease, rheumatoid arthritis, autoimmune poly-endocrinopathy-candidiasis-ectodermal dystrophy) and metabolic diseases (galactosemia) [21,24,25]. Some cases of POF are syndromic, i.e., in Turner syndrome, carbohydratedeficient glycoprotein syndromes, pseudohypoparathyroidism type 1a, progressive external ophthalmoplegia, autoimmune polyglandular syndrome type I, and ovarian leukodystrophy [21].…”
Section: Premature Ovarian Failure: the Terminologymentioning
confidence: 99%
See 2 more Smart Citations